2016
DOI: 10.1039/c6ta05903a
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and selective oxidation of sulfur mustard using singlet oxygen generated by a pyrene-based metal–organic framework

Abstract: A pyrene-based metal-organic framework (MOF) NU-1000 was used as a heterogeneous photocatalyst for the degradation of a sulfur mustard simulant, 2-chloroethyl ethyl sulfide (CEES). Using irradiation from a commercially available and inexpensive ultraviolet (UV) light-emitting diode (LED), singlet oxygen (1O2) is generated by NU-1000 and selectively oxidizes CEES to the nontoxic product 2-chloroethyl ethyl sulfoxide (CEESO). More importantly, this method was tested on the warfare agent sulfur mustard (HD) for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
150
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 162 publications
(157 citation statements)
references
References 68 publications
2
150
5
Order By: Relevance
“…Particularly interesting has been the study of polypropylene peroxides using dimethyl sulfide (DMS); previous reports demonstrate DMS reacts quickly with polymer peroxides to form dimethyl sulfoxide . This reaction has significant implications in CWA decontamination particularly as bis(2‐chloroethyl) sulfide, also known as sulfur mustard (HD) gas, may be oxidized via its sulfide moiety into a less toxic, sulfoxide byproduct . Furthermore, peroxides are a key reagent in many decontamination methods …”
Section: Resultsmentioning
confidence: 99%
“…Particularly interesting has been the study of polypropylene peroxides using dimethyl sulfide (DMS); previous reports demonstrate DMS reacts quickly with polymer peroxides to form dimethyl sulfoxide . This reaction has significant implications in CWA decontamination particularly as bis(2‐chloroethyl) sulfide, also known as sulfur mustard (HD) gas, may be oxidized via its sulfide moiety into a less toxic, sulfoxide byproduct . Furthermore, peroxides are a key reagent in many decontamination methods …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the overoxidation process to sulfone has been also described as a limitation to be overcome. However, although the use of materials in the sulfoxidation reactions has been explored, [14][15][16][17][18][19][20][21][22] several limitations have been frequently described, such as the use of high powered light energy (> 150 W), [14] materials decorated with toxic metals, [16] non-green solvents and moderate recyclability. [8][9][10][11][12][13] Therefore, an alternative oxidation for the use of peracids and peroxides is the application of gaseous reagents that allows the development of greener processes by reducing the waste from purification, because excess of gas can be easily removed from the reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Although in most cases the use of oxygen for the oxidation of sulfides has been carried out with homogeneous systems, the use of heterogeneous materials, especially those containing porosity in their structure, seems one of the most logical approaches for the use of gases in catalysis. However, although the use of materials in the sulfoxidation reactions has been explored, [14][15][16][17][18][19][20][21][22] several limitations have been frequently described, such as the use of high powered light energy (> 150 W), [14] materials decorated with toxic metals, [16] non-green solvents and moderate recyclability. [16] Overcoming such drawbacks would be highly desirable in order to achieve a green process.…”
Section: Introductionmentioning
confidence: 99%
“…[16] Meanwhile,periodic integration of pyrene,an efficient photosensitizer to generate singlet oxygen ( 1 O 2 ), makes PFC-1 apromising material for photodynamic therapy (PDT). [17] Thec oncurrence of ap ermanent void space and aphotoactive moiety in the structure inspired us to investigate the synergistic chemo-photodynamic therapy with PFC-1. Herein, we demonstrated that the size of PFC-1 can be precisely tuned from the micrometer-scale to the nanoscale, and doxorubicin (Doxo) was successfully encapsulated in Nano-PFC-1 with ah igh uptake of 26.5 wt %.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore,i no ur attempts to target arobust HOF,w echose 1,3,6,8-tetrakis (p-benzoic acid) pyrene (H4TBAPy), aplanar molecule with very large p-conjugated system and four carboxylate acid groups,a sab uilding block. [17] Thec oncurrence of ap ermanent void space and aphotoactive moiety in the structure inspired us to investigate the synergistic chemo-photodynamic therapy with PFC-1. [16] Meanwhile,periodic integration of pyrene,an efficient photosensitizer to generate singlet oxygen ( 1 O 2 ), makes PFC-1 apromising material for photodynamic therapy (PDT).…”
mentioning
confidence: 99%